2012
DOI: 10.1111/j.1600-0625.2012.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Sézary cells to TNF‐α‐induced apoptosis is mediated in part by a loss of TNFR1 and a high level of the IER3 expression

Abstract: Failure to execute an apoptotic program is one of the critical steps and a common mechanism promoting tumorogenesis. Immediate early responsive gene 3 (IER3) has been shown to be upregulated in several cancers. IER3 is a stress induced gene, which upregulation leads to reduction in production of reactive oxygen species (ROS) protecting malignant cells from apoptosis. We observed that malignant lymphocytes from patients with Sézary syndrome (SzS) were resistant to pro-apoptotic dose of tumor necrosis factor-α (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…It is reported that IER3 upregulation is correlated with a decrease level of intracellular ROS and low TNFR1 expression on malignant lymphocytes. Targeting IER3 could be of interest for the development of future therapeutic strategies for patients with Sezary syndrome (Akilov et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that IER3 upregulation is correlated with a decrease level of intracellular ROS and low TNFR1 expression on malignant lymphocytes. Targeting IER3 could be of interest for the development of future therapeutic strategies for patients with Sezary syndrome (Akilov et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is three hypothesis that was gotten scholars' consensus. The fist one is that IER3 gene may combine FIFOATP complex in mitochondria, which regulates the level of the ATP and active oxygen free radicals (ROS) whose role is very important in cancer cells' apoptosis (Akilov et al, 2012). Another mechanism is involved in cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Positive IER3 expression is associated with good prognosis in ovarian cancer, where IER3 functions as a proapoptotic factor to restrict tumor growth (18,19). On the contrary, a high level of IER3 expression appears to link poor survival of patients with multiple myeloma (20)(21)(22)(23)(24)(25), Sézary syndrome (26)(27)(28), and breast cancer (29), in part due to a prosurvival effect of IER3 on cancer cells. In myelodysplastic syndromes, IER3 expression increases gradually with disease development toward acute myeloid leukemia (23,24).…”
Section: Ier3 Supports Krasmentioning
confidence: 99%
“…However, since IER3 is a multifunctional factor, additional work is required to define whether this protein exerts additional protumoral effects through interference with other signaling pathways, in particular NF-κB (10,48) and PI3K/AKT (17). Similarly, with respect to cellular mechanisms, it is possible that this protein additionally modulates pancreatic carcinogenesis by modifying immunological responses (49,50) and apoptosis (10,11,28,51), which are well-characterized players in the process of pancreatic cell transformation. Thus, our present findings not only extend the existing knowledge in the field, but also generate the rational for additional studies.…”
Section: G12dmentioning
confidence: 99%